Pemetrexed versus erlotinib in pretreated patients with advanced non–small cell lung cancer: A Hellenic Oncology Research Group (HORG) randomized phase 3 study. Issue 15 (9th May 2013) - Karampeazis, Athanasios; Voutsina, Alexandra; Souglakos, John; Kentepozidis, Nikos; Giassas, Stelios; Christofillakis, Charalambos; Kotsakis, Athanasios; Papakotoulas, Pavlos; Rapti, Ageliki; Agelidou, Maria; Agelaki, Sofia; Vamvakas, Lambros; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND In this superiority study, pemetrexed was compared with erlotinib in pre‐treated patients with metastatic non–small cell lung cancer (NSCLC). METHODS Patients with stage IIIB/IV NSCLC who progressed after first‐line or second‐line treatment were randomized to receive either pemetrexed or erlotinib. In total, 21.7% of patients in the pemetrexed arm and 23.5% of patients in the erlotinib arm had squamous cell histology, and treatment was third line in 39.2% and 46.4% of patients, respectively. The primary study endpoint was time to tumor progression (TTP). Epidermal growth factor receptor/v‐Ki‐ras2 Kirsten rat sarcoma viral oncogene homolog (EGFR/KRAS) mutation status also was investigated. RESULTS There was no difference in terms of the TTP (P = .195), the objective response rate (P = .469), or overall survival (P = .986) between the 2 treatment arms. In patients who had squamous cell histology, erlotinib resulted in a superior TTP compared with pemetrexed (4.1 months vs 2.5 months, respectively; P = .006). The incidence of grade 3 and 4 neutropenia, thrombocytopenia, and asthenia was significantly higher in the pemetrexed arm, whereas the incidence of grade 3 and 4 skin rash was higher in the erlotinib arm. CONCLUSIONS Both pemetrexed and erlotinib had comparable efficacy in pre‐treated patients with metastatic NSCLC, and the current results indicated that genotyping of tumor cells may have an important effect on treatment efficacy. Cancer 2013;119:2754–2764. © 2013 American Cancer Society.